Perancangan Sistem Informasi Akuntansi Berbasis Microsoft Access Pada Apotek Samaritan - Muhammad Taufik; Sarah Hanifa (ConCEPt - Conference on Community Engagement Project, 2021)
The Apotek Samaritan Singkawang uses a manual accounting system so that the information required cannot be on time, and can even lead to neglect of relevant and faithful representation. Therefore, our community service aims to design and produce a computerized accounting information system using Microsoft Access. We have conducted in-depth interviews with pharmacy owners and field observations. The resulting accounting information system includes a list of accounts forms, customer forms, inventory forms, supplier forms, purchase forms, debt payment forms, sales forms, general journal forms, and inventory adjustment forms. In addition, financial reports include balance statements, income statements, statements of financial statements, statements of changes in capital, purchase reports, sales reports, ending inventory reports, and accounts payable reports. All information systems are integrated with each other and become a relational database. Thus, the implementation of this community service has succeeded in improving the quality of bookkeeping of the Samaritan Singkawang Pharmacy, and can even be adopted by similar industries.